INITIATING LAW REFORM IN INDONESIA (FROM THE DIGNIFIED JUSTICE PERSPECTIVE) - Indah S, Christina Maya; Prasetyo, Teguh (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
It is argued in this article that a study on the law reform of a country is the study which related to understanding of a scientific paradigm which made up of the basic idea of a country’s legal system. The main argument in this article is that the basic idea ofma legalmrefom on a legal system must be build upon the enforcement of the juridical principles found and developed in the system. This is derived from a postulate of the Dignified Justice teory perspective.In this view legal virtues underpinning a legal system are examined together as one system of principles and rules or a legal system. Philosophically, or it is a theoretical and a paradigm that law is believed as inseparable from the legal science itself. This philosophy has been developed to make a correction to the sociological jurisprudence perspective, which mainly argued that each occurence of social changes in a legal system cannot be answered by regulation alone. The sociological jurisprudence point of view argues that law is confined to the status quo of a society. Many has argued that this sociological indicative has occurred in many civil law systems, in particular Indonesia, to be used as its best prototype. In the Indonesian legal system, law is positioned as rules and regulations made by the legislative branch of the government. In this perspective laws has been excluded from humanity almost altogether. This article argues that Pancasila as the Indonesia Legal System is the way to solve this problem. Since Pancasila is used as the basis of the State and the source of all legal sources. For this reason, it is interesting to examine how the Pancasila actually became a basis of values in initiating the project of law reform in Indonesia.